Extremely Low Density and Super‐Compressible Graphene Cellular Materials. Issue 36 (21st July 2017) - Qiu, Ling; Huang, Bing; He, Zijun; Wang, Yuanyuan; Tian, Zhiming; Liu, Jefferson Zhe; Wang, Kun; Song, Jingchao; Gengenbach, Thomas R.; Li, Dan
Abstract : Development of extremely low density graphene elastomer (GE) holds the potential to enable new properties that traditional cellular materials cannot offer, which are promising for a range of emerging applications, ranging from flexible electronics to multifunctional scaffolds. However, existing graphene foams with extremely low density are generally found to have very poor mechanical resilience. It is scientifically intriguing but remains unresolved whether and how the density limit of this class of cellular materials can be further pushed down while their mechanical resilience is being retained. In this work, a simple annealing strategy is developed to investigate the role of intersheet interactions in the formation of extreme‐low‐density of graphene‐based cellular materials. It is discovered that the density limit of mechanically resilient cellular GEs can be further pushed down as low as 0.16 mg cm −3 through thermal annealing. The resultant extremely low density GEs reveal a range of unprecedented properties, including complete recovery from 98% compression in both of liquid and air, ultrahigh solvent adsorption capacity, ultrahigh pressure sensitivity, and light transmittance. Abstract : Graphene cellular elastomers with a density as low as 0.16 mg cm −3, super‐compressability, ultrahigh solvent adsorption capacity, ultrahigh pressure sensitivity, and light transmittance can be fabricated by engineering the intersheet interactions of hierarchically structured graphene cellular materials.